Mercury content in wetland rice soil and water of two different seasons at small-scale gold mine processing areas - T Sugianti; F Zulhaedar; S F Batubara (Brawijaya University, 2016)
This study was aimed to identify the impact of small-scale gold processing activities on mercury content in wetland rice soil and water during the rainy and first dry seasons in Central Lombok and West Lombok Districts. The method used for this study was survey method. Measurement of mercury levels in water samples was conducted at Agro Bogor Centre using SNI 6989.77: 2011methods. The data was collected and processed in a simple statisticpresented descriptively, in order to obtain information. Results of the study showed that mercury content soils in the rainy season exceeded the threshold of 0.005 ppm, while in the first dry season the mercury content in soil decreased, but it was still above the threshold value permitted. The contents of mercury in water samples in the rainy season and the first dry season were still at a safe point that was less than 0.05 ppm. The wetland rice soil and water had been polluted with mercury, although the mercury content in the water was still below the threshold, but the accumulation of mercury that could have been absorbed by the plants are of particular concerns. The decrease of mercury content in soil in dry season was due to lack of gold processing activities.